Adaptive load-based contention window-MAC protocol for underwater wireless sensor networks - Meng Shan; Min Ouyang; Jiyi Wu; Tong Wang (Intelligent and Converged Networks)
In Underwater Wireless Sensor Networks (UWSNs), protocols with definite contention windows fail to adapt to changing network conditions, resulting in channel congestion and collisions. This paper introduces the Adaptive Load-based Contention Window Medium Access Control (ALCW-MAC) protocol, which improves the backoff mechanism of the Contention Window Medium Access Control (CW-MAC) protocol. The ALCW-MAC protocol calculates a collision busy factor to evaluate the system load more accurately and dynamically adjusts the contention window size based on the average collision rate and channel busy rate. These dynamic adjustments enable the protocol to reflect real-time network loads, resulting in channel congestion reduction and bandwidth efficiency improvement. Comprehensive experimental results confirm that ALCW-MAC surpasses CW-MAC in throughput and packet loss rate, significantly enhancing network performance and stability.